Controlling morphologies of Bi 2S 3 nanostructures synthesized by glycolthermal method - Anukorn Phuruangrat (2018)
Single crystalline orthorhombic Bi2S3nanostructures with different morphologies were synthesized by the 180 °C and 12 h glycolthermal reactions, using ethylene glycol, propylene glycol and polyethylene glycol with different molecular weights as solvents. The as-synthesized products were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), high resolution transmission electron microscopy (HRTEM), and selected area electron diffraction (SAED). In the present research, different solvents played the role in the product morphologies. A formation mechanism of Bi2S3nanostructures was also proposed. © 2011 Elsevier B.V. All rights reserved.